Students' creative thinking skills through creative problem solving learning model - Fatma Zuhra; Nurhayati Nurhayati; Jasmaniah Jasmaniah; Nanda Safarati (Universitas Pendidikan Ganesha, 2025)
Creative thinking skills (KBK) are important for students to understand concepts as a whole so they can interpret learning concepts well in order to make students successful in their learning process so they can obtain better learning outcomes. CPS is a learning model that has an influence on KBK because of its advantages, namely making it easier for students to solve problems, design an invention, and evaluate the results of the invention. The aim of this research is to determine the increase in students' KBK through the implementation of the CPS learning model. This research is a type of quasi-experimental research with a quantitative approach with a one group pretest-posttest design. This research uses a saturated sampling technique where the population and sample in this research are all class IV students at SD Negeri 1 Kuala totaling 23 students. The instrument used in this research is a test instrument which is prepared based on CBC indicators. Data analysis using SPSS version 23. The results show a Sig value. < 0.05, namely 0.00, thus Ho is rejected and Ha is accepted, it can be concluded that there is an increase in students' KBK through the implementation of the CPS learning model.